Role of Tumor-Associated Macrophages in Different Grades of Oral Squamous Cell Carcinoma: An Institutional Study - Sreepreeti Champatyray; Saurjya Ranjan Das; Dhiren Kumar Panda (Disease and Health Research: New Insights Vol. 9, 2024)
Aims: This study aims to evaluate the expression of Tumor-Associated Macrophages (TAMs) in different grades of Oral Squamous Cell Carcinoma (OSCC) and determine the association between TAM expression and clinical parameters such as local recurrence and metastasis. Methodology: The study was conducted on fifty tumor biopsy samples of OSCC in T1N0M0 and T2N0M0 stages. Additionally, ten biopsy specimens of normal oral mucosa, collected during minor oral surgical procedures with patient consent, were included as controls. TAM infiltration was evaluated using Hematoxylin & Eosin (H&E) staining and immunohistochemistry (IHC) techniques. The data were statistically analyzed using SPSS software. Results: The findings revealed that TAMs, particularly those of the M2 phenotype, were associated with local recurrence, metastasis, and survival in OSCC cases. Higher TAM expression was correlated with shorter survival rates and increased aggressiveness of the tumor. A statistically significant correlation was observed between TAM expression and TNM staging (p < 0.0001). TAM infiltration was found to increase from well-differentiated to poorly differentiated OSCC, indicating a potential role in tumor progression. Moreover, a significant difference in TAM expression was noted between OSCC tissues and normal oral mucosa (p < 0.002). Conclusion: The study highlights the significant role of TAMs in OSCC progression and their potential as prognostic markers. Since metastases are a principal cause of mortality in cancer patients, understanding TAM-mediated tumor invasion and metastasis is crucial for developing new therapeutic targets. Future research should employ advanced diagnostic methods, such as specific IHC markers (e.g., CD68), with larger sample sizes to validate these findings.